Global governance and the broader determinants of health: A comparative case study of UNDP's and WTO's engagement with global health. Issue 2 (1st February 2019) - Gopinathan, Unni; Watts, Nick; Lefebvre, Alexandre; Cheung, Arthur; Hoffman, Steven J.; Røttingen, John-Arne
ABSTRACT: This comparative case study investigated how two intergovernmental organisations without formal health mandates – the United Nations Development Programme (UNDP) and the World Trade Organization (WTO) – have engaged with global health issues. Triangulating insights from key institutional documents, ten semi-structured interviews with senior officials, and scholarly books tracing the history of both organisations, the study identified an evolving and broadened engagement with global health issues in UNDP and WTO. Within WTO, the dominant view was that enhancing international trade is instrumental to improving global health, although the need to resolve tensions between public health objectives and WTO agreements was recognised. For UNDP, interviewees reported that the agency gained prominence in global health for its response to HIV/AIDS in the 1990s and early 2000s. Learning from that experience, the agency has evolved and expanded its role in two respects: it has increasingly facilitated processes to provide global normative direction for global health issues such as HIV/AIDS and access to medicines, and it has expanded its focus beyond HIV/AIDS. Overall, the study findings suggest the need for seeking greater integration among international institutions, closing key global institutional gaps, and establishing a shared global institutional space for promoting action on the broader determinants of health.